Epidemiological studies of Fasciola gigantica infections in cattle in the highveld and lowveld communal grazing areas of Zimbabwe - D.M. Pfukenyi; Pfukenyi Mukaratirwa; A.L. Willingham; J. Monrad (Onderstepoort Journal of Veterinary Research, 2006)
During the period between January 1999 and December 2000, the distribution and seasonal patterns of Fasciola gigantica infections in cattle in the highveld and lowveld communal grazing areas of Zimbabwe were determined through monthly coprological examination. Cattle faecal samples were collected from 12 and nine dipping sites in the highveld and lowveld communal grazing areas respectively. Patterns of distribution and seasonal fluctuations of the intermediate host-snail populations and the climatic factors influencing the distribution were also determined by sampling at monthly intervals for a period of 24 months (November 1998 to October 2000) in six dams and six streams in the highveld and in nine dams in the lowveld communal grazing areas. Each site was sampled for relative snail density and the vegetation cover and type, physical and chemical properties of water, and mean monthly rainfall and temperature were recorded. Aquatic vegetation and grass samples 0-1 m from the edges of the snail habitats were collected monthly to determine the presence or absence of F. gigantica metacercariae. Snails collected at the same time were individually checked for the emergence of larval stages of F. gigantica. A total of 16 264 (calves 5 418; weaners 5 461 and adults 5 385) faecal samples were collected during the entire period of the study and 2 500 (15.4 %) of the samples were positive for F. gigantica eggs. Significantly higher prevalences were found in the highveld compared to the lowveld (P < 0.001), for adult cattle than calves ( P < 0.01) and in the wet season over the dry season (P < 0.01). Faecal egg output peaked from August / September to March / April for both years of the study. Lymnaea natalensis, the snail intermediate host of F. gigantica was recorded from the study sites with the highveld having a significantly higher abundance of the snail species than the lowveld (P < 0.01). The snail population was low between December and March and started to increase in April reaching a peak in September / October. The number of juvenile snails peaked between April and August. The mean number of snails collected was negatively correlated with rainfall and positively correlated with temperature. Mean number of snails collected was also positively correlated with Potamogeton plant species and negatively correlated with Cyperus plant species. However, none of the L. natalensis collected from the habitats were found shedding Fasciola cercariae. Metacercariae were found on herbage from the fringes of the snail habitats between February and August for both years, with most of the metacercariae concentrated on herbage 0-1 m from the banks of the habitats. Based on the findings of this study, anthelmintic treatment should be administered in December / January to control chronic and mature fasciolosis. A second treatment should be given in April / May to reduce pasture contamination and subsequently snail infection, as this is the time the snail population starts to build up. To control acute fasciolosis due to the immature liver flukes a third treatment should be given in August. The first application of molluscicides to control the snail intermediate hosts can be done in June the time when the snail is harbouring the parasite and a second application in September in order to kill new generations of infected snails.